Explanatory Injustice and Epistemic Agency - Mitova, Veli (Ethical theory and moral practice, 2020)
What is going on when we explain someone’s belief by appeal to stereotypes associated with her gender, sexuality, race, or class? In this paper I try to motivate two claims. First, such explanations involve an overlooked form of epistemic injustice, which I call ‘explanatory injustice’. Second, the language of reasons helps us shed light on the ways in which such injustice wrongs the victim qua epistemic agent. In particular, explanatory injustice is best understood as occurring in explanations of belief through a so-called reason-why when the correct explanation in fact features a motivating reason. I reach this conclusion by arguing that such explanations are a kind of normative inversion of confabulation. Thinking in these terms helps us see both how certain reason-ascriptions empower while others disempower, and (consequently) how through them believers are robbed of agency over their beliefs.